2023
DOI: 10.1101/2023.02.10.23285794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Concurrent Transcranial Magnetic Stimulation and Electroencephalography Measures are Associated with Antidepressant Response from rTMS Treatment for Depression

Abstract: Background Response rates to repetitive transcranial magnetic stimulation (rTMS) for depression are 25-45%. Biomarkers predicting response to rTMS may reduce treatment burden. TMS-evoked neural activity recorded via electroencephalography (EEG) has potential as a biomarker of treatment response. We examined whether these measures could differentiate responders and non-responders to rTMS for depression. Methods Thirty-nine patients with treatment-resistant major depressive disorder (MDD) and 21 healthy controls… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
1
0
0
Order By: Relevance
“…Several clinical disorders, including anxiety and depression, are believed to be associated with E/I ratio uncoupling and the resulting disordered prefrontal oscillatory phase coherence (Lisman, 2012; Radhu et al, 2014; Voineskos et al, 2019; Yizhar et al, 2011). The altered E/I ratio following TMS applied to the DLPFC of meditators may suggest a potential target for therapeutic interventions, where therapies could aim to adjust the E/I ratio in a way that might relate to improvement of clinical symptoms following a mindfulness intervention (Piet & Hougaard, 2011; Strauss et al, 2014), Interestingly, recent research has suggested that a steeper N100 slope (driven by a larger P60 amplitude) is found in individuals who respond to TMS treatment for depression, a finding that may be analogous to our finding of a larger P60/N100 ratio in the current research, highlighting a potential clinical implication of the current study (Bailey et al, 2023d).…”
Section: Discussionsupporting
confidence: 81%
“…Several clinical disorders, including anxiety and depression, are believed to be associated with E/I ratio uncoupling and the resulting disordered prefrontal oscillatory phase coherence (Lisman, 2012; Radhu et al, 2014; Voineskos et al, 2019; Yizhar et al, 2011). The altered E/I ratio following TMS applied to the DLPFC of meditators may suggest a potential target for therapeutic interventions, where therapies could aim to adjust the E/I ratio in a way that might relate to improvement of clinical symptoms following a mindfulness intervention (Piet & Hougaard, 2011; Strauss et al, 2014), Interestingly, recent research has suggested that a steeper N100 slope (driven by a larger P60 amplitude) is found in individuals who respond to TMS treatment for depression, a finding that may be analogous to our finding of a larger P60/N100 ratio in the current research, highlighting a potential clinical implication of the current study (Bailey et al, 2023d).…”
Section: Discussionsupporting
confidence: 81%